ANALISIS KORELASI ANTARA EKUITAS MEREK DENGAN KEPUTUSAN KONSUMEN DALAM MEMBELI MOBIL TOYOTA AVANZA PADA PT HADJI KALLADI KOTA MAKASSAR - Asdi . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2017)
This studyaims to determinehow the influence ofbrand equityon consumer decisionin buyinga Toyota Avanza in Makassar. The study was conducted at PT Hadj iKalla Alauddin Makassar branch, with 100 consumers capture samples, selected at random, using the technique of questionnaireas data collection techniques.To describe thecharacteristics of the respondentsused the analytical techniquespercentage, whiledescribingthe research variablesusinganalysis techniques; Simple linear regression, the product moment correlation, coefficientof determination, and asignificance testt test.The result showedthat; correlation coefficient (r) =0.899 means that the correlation between the variables of brand equity (X) with the purchase decision variable (Y) is very strong, while the coefficient of determination(KP) =0.808 means that the brand equity variable (X) effect amounted to 80.8% variable in the consumer's decision to buy a Toyota Avanza (Y), with the remaining 20.8% is influenced by other variables not examined in this study. While significant testing by t-test showed that t hitung 20.317 is greater than t table of 2.63 at the significance level of 5% (20.317>2.63), meaning that the value obtained is significant that the hypothesis can be accepted.Keywords: Brand Equity, Purchase Decision